2011
DOI: 10.1021/jf203778z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Antioxidant Properties of Casein Peptide and Its Glucose Maillard Reaction Products in Fish Oil-in-Water Emulsions

Abstract: Maillard reaction products (MRPs) were prepared by reacting casein peptides with different concentrations of glucose at 80 °C for up to 12 h. The chemical properties of MRPs and their effects on lipid oxidation in fish oil-in-water emulsions were investigated. Increasing browning development and absorbance in 294 nm in the MRPs caused an increase in DPPH radical scavenging, but a decrease in iron chelation, which could be related to the loss of free amino groups in the peptides. The MRPs produced with longer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Casein micelles and CD micelles are observed to reduce the absorbance of ABTS + at 734 nm, which is due to hydrogen donor groups of indole, phenyl, and imidazole in amino acid residues such as tryptophan and methionine cysteine. [44,45] Although curcumin rapidly degrades at physiological pH, the recent work revealed that curcumin itself, instead of its degradation products, is largely responsible for the observed biological actions of curcumin. [46] The high effectiveness of radical scavenging ability of curcumin is mainly contributed by its phenolic groups, which could scavenge ABTS + radical by donating their H atoms.…”
Section: Stability and Antioxidant Activity Of Curcumin With CD Micellesmentioning
confidence: 99%
“…Casein micelles and CD micelles are observed to reduce the absorbance of ABTS + at 734 nm, which is due to hydrogen donor groups of indole, phenyl, and imidazole in amino acid residues such as tryptophan and methionine cysteine. [44,45] Although curcumin rapidly degrades at physiological pH, the recent work revealed that curcumin itself, instead of its degradation products, is largely responsible for the observed biological actions of curcumin. [46] The high effectiveness of radical scavenging ability of curcumin is mainly contributed by its phenolic groups, which could scavenge ABTS + radical by donating their H atoms.…”
Section: Stability and Antioxidant Activity Of Curcumin With CD Micellesmentioning
confidence: 99%
“…40 As for the antioxidant activity in the cell system, Chung et al 17 reported that the antioxidant activity of MRPs prepared by heating a mixture of rice starch with different dextrose and glycine in Caco-2 cells was coincidental with the increase in its browning intensity. 42 These conflicting data on the antioxidant activity of MRPs may be a result of the complicated components of melanoidin fractions, as well as the assays used to measure these activities. Our previous research also showed that MRPs from the heated casein peptide and glucose against inhibiting lipid oxidation in fish oil-in-emulsions were not related to the browning intensity.…”
Section: Relationship Between Antioxidant Activity and Chemical Propementioning
confidence: 99%
“…Since samples prepared with mixed sugar had higher extent Maillard reaction than samples prepared with sucrose because of an accelerating of reducing fructose (Laroque et al 2008). Some derivative compounds produced by Maillard reaction in sample prepared with mixed sugar could retard lipid oxidation (Dong et al 2011;Zamora and Hidalgo 2005). The lowest TBA value was observed in samples stored in vacuum condition (p < 0.05) which was confirmed by high sensory scores in rancidity attributes (Fig.…”
Section: Resultsmentioning
confidence: 68%